The myth of sex addiction - Ley, David J., 1973- (Rowman & Littlefield Publishers, 2012)
"In this controversial new book, David Ley debunks the myth of sex addiction, showing how labeling it a disorder has wrested responsibility away from philandering men and excused their bad behavior as being out of their control. He takes on those who would label it a disease and challenges us to reexamine our approach to male sexuality."--Provided by publisher